On Intuitionistic Fuzzy Almost Regular ⍺ Generalized Continuous Mappings - Jayanthi D, Nivetha M, (International Journal of Scientific Research and Management (IJSRM), 2015)
The purpose of this paper is to introduce and study the concept of intuitionistic fuzzy almost regular α generalized continuous mapping in intuitionistic fuzzy topological spaces and study some of their properties.